Pengaruh Sikap, Norma Subjektif, dan Kontrol Perilaku terhadap Intensi Mahasiswa FEB Unila untuk Berinvestasi Airdrop Token Cryptocurrency - Anzeli Hayatun Nuffus; Pigo Nauli (AKUNTANSI 45, 2026)
This study aims to analyze the influence of attitude, subjective norms, and perceived behavioral control on the intention of students of the Faculty of Economics and Business, University of Lampung, to use cryptocurrency airdrop tokens. This research is motivated by the increasing interest of young generations in cryptocurrency. The study employed a quantitative approach based on the Theory of Planned Behavior (TPB). The population consisted of FEB University of Lampung students who had experience participating in cryptocurrency airdrops through Telegram. The sampling technique used purposive sampling, and data were collected through questionnaires. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with SmartPLS software.The results indicate that attitude and subjective norms have a positive and significant effect on students’ intention to participate in cryptocurrency token airdrops through Telegram. Positive attitudes toward the benefits of airdrops and social support from peers, digital communities, and the surrounding environment are the main factors encouraging students to participate in token airdrops. However, perceived behavioral control does not have a significant effect on students’ intentions. This finding indicates that students’ perceptions regarding their ability, knowledge, and control in using airdrop tokens are not sufficient to increase their intention to participate. The study demonstrates that psychological and social factors are more dominant than behavioral control factors in influencing students’ intentions toward cryptocurrency-based digital investment. This research is expected to contribute to the development of digital financial literacy and serve as a reference for educational strategies related to cryptocurrency investment among university students.